TEOLOGI ISLAM DAN HAK ASASI MANUSIA DALAM PEMIKIRAN ABDULLAHI AHMED AN-NA’IM - Budiman, Arman (Rausyan Fikr: Jurnal Ilmu Studi Ushuluddin dan Filsafat, 2024)
Researchers have widely discussed research on human rights, but there has not been much writing that specifically connects the theological aspects with practical aspects. This research examines the construction of Ahmed An-Na'im's theology and its relevance to the problems of modern society. This article is literature research that examines the thoughts of figures through historical analysis. The primary data is an essay by the figure studied, Abdullahi Ahmed An-Nai'im: Toward an Islamic Reformation: Civil Liberties, Human Rights and International Law, Islam and the Secular State. Meanwhile, secondary sources are other works that discuss An-Na'im's thoughts, human rights, and Islamic theology. This research concludes that An-Na'im made the Universal Declaration of Human Rights a strong instrument to protect the glory, honor, and dignity of every human being on Earth. This research makes an important contribution as a theological and practical basis for eliminating all forms of human rights violations and making human values ​​the main element in law and social interaction in social and state life.